2015
DOI: 10.1016/j.chembiol.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Modularity of RiPP Enzymes Enables Designed Synthesis of Decorated Peptides

Abstract: SUMMARY Macrocyclases and other posttranslational enzymes afford derived peptides with improved properties for pharmaceutical and biotechnological applications. Here, we asked whether multiple posttranslational modifications could be simultaneously controlled and matched to rationally generate new peptide derivatives. We reconstituted the cyanobactin peptide natural products in vitro with up to five different posttranslational enzymes in a single tube. By manipulating the order of addition and identity of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
143
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 44 publications
2
143
0
Order By: Relevance
“…Many RiPPs undergo enzymatic macrocyclization, as observed in several diverse classes of compounds including bottromycins (11), cyanobactins (12), lanthipeptides (13), streptides (14), lasso peptides (15), and thiopeptides (16). Understanding the biosynthetic pathways for RiPP macrocyclization continues to be important for biotechnological application, for the identification of new gene clusters, and for the production of novel RiPP derivatives (17).…”
mentioning
confidence: 99%
“…Many RiPPs undergo enzymatic macrocyclization, as observed in several diverse classes of compounds including bottromycins (11), cyanobactins (12), lanthipeptides (13), streptides (14), lasso peptides (15), and thiopeptides (16). Understanding the biosynthetic pathways for RiPP macrocyclization continues to be important for biotechnological application, for the identification of new gene clusters, and for the production of novel RiPP derivatives (17).…”
mentioning
confidence: 99%
“…Previously, we showed that the rates of purified enzymes alone or in combination were not affected by DMAPP concentration (11). We used a series of vectors leading to different isoprene products, demonstrating that the increased yield could be observed no matter whether DMAPP, isopentenyl pyrophosphate, or farnesyl pyrophosphate was the primary product of the pathway (Fig.…”
Section: Mechanism 4: Modulation Of Protein Activity Underlies the Cymentioning
confidence: 72%
“…A mixture of patellins with 0-2 units of isoprene was produced, and prenylation increased slowly over a series of days. Therefore, we increased production of the isoprene precursor, dimethylallylpyrophosphate (DMAPP), using the vector pMBI, which contains genes (mev) that convert mevalonic acid to DMAPP (17), which in turn is a substrate for prenyltransferase TruF1 (11). Coexpression of pTru-SD and pMBI led to a great increase in prenylation that depended on the dose of added mevalonate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations